Kenaf and rice husk filled polypropylene composites containing ammonium polyphosphate - Ismail, Atikah (2013)
The main objective of this study was to investigate and compare the effects of kenaf and rice husk fibers content on flammability, mechanical, thermal and morphology properties of polypropylene (PP) composites. The effects of ammonium polyphosphate (APP) content on mechanical and flammability properties of untreated and treated fibers filled PP composites were also investigated. The composites were prepared using a co-rotating twin screw extruder for compounding process and followed by compression molding for test specimen preparation. Rice husk and kenaf fibers were treated by alkaline treatment to modify the fiber surface. Cone calorimeter and limiting oxygen index (LOI) test were performed to determine the flammability properties of the samples. Flexural and impact test were done to determine the mechanical properties of PP composites. In addition, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were done to investigate thermal stability of the composites. Addition of APP into PP composites was found to increase the LOI values that indicate the improvement of flame retardancy properties. Whereas, cone calorimeter results showed that incorporation of APP into fibers filled PP composites decreased the heat release rate (HRR) which indicated the improvement of flame retardancy system. Incorporation of APP into PP composites increased the flexural modulus of composites but decreased the flexural strength of composites. On the other hand, the flexural strength of PP composites was observed to increase with the addition of treated fibers. A decrease in impact strength was observed with the addition of APP to PP composites. Incorporation of treated fibers into PP composites also decreased the impact strength. From TGA results, it can be observed that the addition of APP into composites enhanced the thermal stability of composites at high temperature and increased the formation of char residue. The addition of APP in the fibers filled PP composites increased the crystallization temperature of composites. Morphological studies showed that both fibers that underwent alkaline treatment improved the fibers dispersion in the composites and also resulting in better mechanical properties. In this study, it was showed that addition of APP as flame retardant improved the flame retardancy of PP composites. Besides the improvement in flame retardancy properties, the alkaline treatment on rice husk and kenaf fiber has proven to show the better mechanical properties of PP composites.